The Kheri Maneaters - Choudhury, S. R.; Sinha, J. P. (Indian Forester, 1980)
The authors made on the spot study of the problem of maneating in the Kheri district of Uttar Pradesh. In this district, a major ecological change has been brought in by man in the earsthwhile rich alluvial grass lands and mixed terai forests. These grass land forests have, during the past to decades, been extensively replaced by, prosperous sugar cane. The farmers are by and large immigrants displaced from Pakistan. They live a highly sophisticated life. The resident tigers of the former natural forests have stuck to small pockets of natural cover along the river systems and operate mostly in the cane fields. The Sardarji feels socially tolerant to these tigers, to some extent appreciative of their role in keeping down the crop depredation by wild boars.In this rationalised relationship of the modern man with the tigers in his cane fields, man eating started suddenly in March 78, at three different localities One of these three, the Satiana maneater, suspected to be a big fema1e was shot in the cane field on 14, 1978 and was found to be a young male. The second, a young female with cubs of successive litters at heel, was shot on human kill on the arrangements made by the authors on May 28, 1979. External features and autopsy of her caracass did not reveal any defect. She was a healthy young female. Her older cub, a 16 17 months old male, was subsequently lost track of. On June 16 the two younger ones, 4-5 months old cubs, Were found in a pit not far from where their mother had been shot. One of those was dead and the other in badly rundown condition died three days later. The third maneater known as the Sarada maneater who started maneating as a sub-adult male and in course of time grew up to leave distinct pugmarks of a big male was still at large during the field study by the authors.The paper had documented details of all kills of each of these three maneaters. Analysis of the data reveals here in Kheri district that, contrary to the accepted notion that disabled tigers only became maneaters, maneating may develop as a habit in ablobodied young and apetitive tigers in socio-ecological conditions as obtain in Kheri district where the tiger operates in the same land of dense human occupation with intensive farming activities.The authors have cleared the tigers of Dudwa National Park of the stigma of maneating which they had been suspected of. They have suggested workable propositions to keep continuos watch on tigers in the cane fields and manage those as a resource for the bilateral benefits to the future of the tiger and the local farmers who live with them here. They also feel that the behaviour of the Sunderbans maneater could be reasonably interpreted through the wisening by the Kheri maneaters.